Cell line specific alterations in genes associated with dopamine metabolism and signaling in midbrain dopaminergic neurons derived from 22q11.2 deletion carriers with elevated dopamine synthesis capacity - Reid, Matthew J.; Rogdaki, Maria; Dutan, Lucia; Hanger, Bjørn; Sabad, Kaarin; Nagy, Roland; Adhya, Dwaipayan; Baron-Cohen, Simon; McAlonan, Grainne; Price, Jack; Vernon, Anthony C.; Howes, Oliver D.; et al. (Schizophrenia Research, 2022)
Microdeletions at the 22q11.2 locus are associated with increased risk for schizophrenia. Recent work has demonstrated that antipsychotic naïve 22q11.2 carriers display elevated levels of dopamine synthesis capacity (DSC) as assessed by 18F-DOPA PET imaging. While this is consistent with a role for abnormal dopamine function in schizophrenia, it is unclear what molecular changes may be associated with this neuro-imaging endophenotype, and moreover, if these alterations occur independently of clinical presentation. We therefore conducted a pilot study in which we generated human induced pluripotent stem cells (hiPSCs) from two 22q11.2 deletion carriers with elevated DSC in vivo, but distinct clinical presentations. From these and neurotypical control lines we were able to robustly generate midbrain dopaminergic neurons (mDA-neurons). We then assessed whether genes associated with dopamine synthesis, metabolism or signaling show altered expression between genotypes and further between the 22q11.2 deletion lines. Our data showed alterations in expression of genes associated with dopamine metabolism and signaling that differed between the two 22q11.2 hiPSC lines with distinct clinical presentations. This reinforces the importance of considering clinical, genetic and molecular information, when possible, when choosing which donors to generate hiPSCs from, to carry out mechanistic studies.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Human induced pluripotent stem cells; Midbrain floor plate neural progenitor; Reprogramming; Schizophrenia; [